Enhancing Financial Literacy Among Non-Financial Employees in the Parenting Tech Industry: A Case Study of PT. Tentang Anak - Suryanto Suryanto; Kartina Natalilova; Annisa Kanti; Nila Pusvikasari (International Journal Of Community Service, 2026)
A lack of understanding regarding the impact of operational activities on financial statements often hinders cash flow efficiency, particularly in fast-paced startup environments. This Community Service (Pengabdian Kepada Masyarakat) activity aimed to enhance the financial literacy of non-financial employees at PT. Tentang Anak through the "Finance 101: Understanding Business Finance" training program. The training was conducted on January 23, 2026, utilizing lecture methods, case study discussions, and measurable evaluations. The material covered basic accounting concepts, the Cash Conversion Cycle (CCC), and company-specific terminology such as Total Product Value (TPV). Evaluation results demonstrated a significant improvement in participant understanding, with the majority of participants achieving post-test scores above 70, compared to varying lower scores in the pre-test. Participants also responded positively regarding the relevance of the material to their daily work, specifically in understanding the urgency of timely financial administration processes.